Penulisan Butir Soal Dengan Artificial intellegence (AI) - Munali, Munali; Liberna, Hawa; Syukriyansyah, Syukriyansyah; Aziiz, Esa Nur (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
Technological developments in 4.0 require people to use the latest technology. The latest technological systems require skilled human resources. The current technological development is artificial intelligence which can do work like humans do. Artificial Intelligence can be used in writing questions. The aim of Community Service is: to assist teachers in writing questions using Artificial Intelligence via the ChatGPT platform. The qualitative research method involves asking several teachers during the activity. Community Service Results, namely: 1) teachers do not understand writing questions using the revised Bloom's Taxonomy at cognitive levels C4, C5, and C6; and 2) teachers can use the question item writing platform with ChatGPT. Based on these results, teachers are given an in-depth understanding of the theory of writing questions at cognitive levels C4, C5, and C6. Through this understanding, teachers are expected to be able to write questions correctly which are supported by ChatGPT. This is because ChatGPT is not completely correct regarding writing question items.